The Ontological Meanings of Dhunnya: Principles of Socio-Religious Harmony in the Lives of Madurese Migrants in Malaysia - Hidayat, Ainur Rahman; Buna’i, Buna’i; Zulaekah, Zulaekah; Harisah, Harisah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This study explores the ontology of dhunnya in Madurese culture, encompassing its interpretations as treasure, the mortal world, and the worldly realm within the framework of intentionality-equilibrium. The concept of dhunnya is inherently directed towards achieving socio-religious balance, which serves as a fundamental guiding principle for the Madurese, both within their homeland and in diasporic contexts. This concept underpins the mindset, attitudes, and behaviors of the Madurese people, who place significant emphasis on spiritual and religious dimensions. This study adopts a hermeneutic-philosophical approach, concluding that the harmony and disharmony of dhunnya are reflected in the balance between rights to property, altruism, and transient worldly adornments. Moreover, this balance is oriented towards fostering ethnic solidarity and strengthening the kiai-santri relationship. The eclectic model of dhunnya ontology is reconstructed through an analysis of socio-religious practices, including koloman, haul, tahlilan, molodhen, funeral rites, and studio-based education. These practices are particularly relevant to the integration of spiritual-religious and spiritual-economic aspects among Madurese migrants in Malaysia. This finding underscores the critical role of socio-religious principles in maintaining the harmony of Madurese life in diaspora contexts.